ESG AND BANKING PERFORMANCE IN EMERGING AND DEVELOPING COUNTRIES: DO ISLAMIC BANKS PERFORM BETTER? - Fakhrunnas, Faaza; Kenc, Turalay; Hengchao, Zhang (Bank Indonesia, 2025)
This paper investigates the effects of Environmental, Social, and Governance (ESG) implementation on banking performance in emerging and developing countries. Applying the Two-step System Generalized Method of Moments (System-GMM) to panel data of 179 banks across 29 countries spanning 2016-2022, we find that ESG implementation significantly enhances overall banking profitability. However, when we assess the implications of ESG on Islamic banks, we find that overall ESG commitment significantly reduces profitability. As for the individual ESG pillar, we note the profit-enhancing effect of environmental pillar on both Islamic and conventional bank profitability. Some evidence is also uncovered for the significant positive effect of social pillar on conventional bank profitability. Finally, we note no significant influences from governance pillar. These results highlight the divergent impacts of ESG implementation on Islamic and conventional banks. We conclude that policymakers should exercise caution in designing and implementing ESG policies, ensuring they are tailored to promote optimal performance across different banking models. This study contributes to the growing body of the literature on sustainable finance and provides valuable insights for regulators and bank managers in emerging and developing economies.